Analisis Faktor-Faktor Yang Mempengaruhi Auditor Switching(Studi Empiris pada Perusahaan Food and Beverage yang Terdaftar di BEI Tahun 2013-2015) - Kafitaria, Ganis, Drs. Atwal Arifin, Akt., M.Si (2017)
Auditor switching is a changes of auditor performed by the client company. This research purposed are to analyze the influence of audit opinion, KAP size, management changes and financial distress on the auditor switching food and beverages companies listed on the Indonesia Stock Exchange. The population used in this study focused on food and beverages companies listed in Indonesia Stock Exchange 2013-2015. Sampling was purposive sampling method that produced 51 companies sample. Data analysis technique used is logistic regression analysis. The results of the study showed that audit opinion affect to the auditor switching. KAP size, management changes, and financial distress has no affect to the auditor switching.